The effect of army vest design on the occurrence of stress fractures and overuse injuries in female military recruits. Issue 4 (30th November 2016) - Palmanovich, Ezequiel; Frankl, M; Nyska, M; Hetsroni, I; Constantini, N; Trejo, L; Bechar, R; Novak, G; Lankovsky, Z; Mann, G
Abstract : Introduction: Stress fractures (SFs) occur when microdamage caused by repetitive mechanical load exceeds the biological load-bearing capacity of the bone. The study objective was to test whether a vest specifically designed and manufactured for female recruits, compared with the standard vest used on a regular basis by Border Police recruits, would reduce the incidence of SF in female Border Police recruits. Data based on reports of military personnel show that women are more likely to sustain SFs. Methods: A follow-up of 240 female Border Police infantry recruits, divided into two trial groups, was conducted from 2007 to 2009. Two different vests were evaluated—the standard special unit fighting vest, which was conventionally used by both men and women during basic training, and the new fighting vest, specially design for female body shape. Results: No significant difference was noted in the number of SFs between the two groups which may be attributed to increased weight of the new vest. There was a lower incidence of long bone SFs which may have been due to the superior vest design. The female Border Police Infantry recruits expressed great satisfaction with the new vest. Conclusions: Increased effort should be invested to further reduce the weight of female combat gear, alongside efforts to improve fit and comfort.